Adequação de metodologias para avaliação da qualidade fisiológica de sementes de chia (Salvia hispanica L.) - Nunes, Joseli Viviane Ditzel (2017)
Chia (Salvia hispanica L.) is an oleaginous plant from Mexico, which was cropped and consumed by the Maya and Aztec peoples since ancient times in order to provide energy, strength and vitality. This seed is a natural source of omega-3, omega-6, fiber, protein, vitamins, as well as other important nutritional components. It helps on preventing cardiovascular diseases, nervous and inflammatory diseases, and diabetes, among others. Its physiological quality is an essential parameter for significant yield of grains and seeds since the demand for chia has increased every year. Thus, this study aimed at adapting methodologies to evaluate seeds physiological quality, checking which tests are more efficient to determine seeds vigor, evaluating mucilage production and if vigor can influence on its produced amount. Thus, seeds were submitted to determine purity, mass of 100 seeds, moisture content, variations on tests such as germination, seedling growth, emergence in sand, accelerated aging, cold test without soil, electrical conductivity, water uptake curve and mucilage extraction. After determining the best methodology for each test, each one of them was carried out for seeds cropped during two cropping years (2013/2014, 2014/2015). Mucilage variation was also evaluated according to these seeds vigor. A completely randomized experimental design was carried out in double and triple factorials, according to the tests. Under tested conditions, it was concluded that chia seeds can germinate in paper and sand substrates, in light presence or absence, under temperatures from 15 to 35 ºC, thus achieving high rates of germination percentage. Seedling length test was developed in gerbox for nine days, the emergence in sand test was obtained with 0.5 cm depth at 25-30 ºC, the accelerated aging test was under 41 ºC, for 36 hours with water and 45 ºC for 12 hours with saturated solution, and electrical conductivity test was recorded with 24 hours, 25 mL water at 25-30 ºC, and they can be used to determine chia seeds vigor. The proposed methodology was efficient to extract chia seeds mucilage and seed vigor did not interfere in the amount of mucilage produced.